Urban ornithology : 150 years of birds in New York City - Buckley, P. A.; Sedwitz, Walter, -1985; Norse, William J., -2006; Kieran, John, 1892-1981 (Cornell scholarship online., 2018)
"A quantitative long-term historical analysis of the migratory, winter, and breeding avifaunas of New York City's Van Cortlandt Park and Northwest Bronx from 1872 to 2016"--Provided by publisher.